INTERVENSI PELATIHAN DAN PENDAMPINGAN UNTUK MENINGKATKAN AKURASI PENGUKURAN ANTROPOMETRI KADER POSYANDU - esti, esti (Khidmah, 2025)
Anthropometric measurement is one of the essential skills for Posyandu cadres in monitoring the growth and nutritional status of toddlers. A lack of skill in performing anthropometric measurements can lead to misinterpretation of nutritional status, which risks incorrect stunting diagnoses. This study aims to improve the skills of Posyandu cadres through training and mentoring in anthropometric measurement in the working area of Puskesmas Sako, Palembang City. The methods used include theoretical and practical training, field mentoring, and evaluations before and after the intervention. The results of the study show a significant improvement in the knowledge and skills of the cadres, with an average score increase of 4.66 points after the training. The conclusion of this study is that continuous training and mentoring of cadres can improve the accuracy of anthropometric measurements and support efforts in stunting prevention and early detection in the community